An investigation on the chloroplast and nuclear genomes of taxa belong to the subgenus dracunculus (Bess.) rydb. of artemisia l. (asteraceae) in turkey - Yilmaz Sancar, P.; Wahid, C.F.; Civelek, S.; Kursat, M. (Instituto Internacional de Ecologia, 2022)
Artemisia is one of the biggest genera in the family Asteraceae, with around 500-600 taxa at specific and sub-specific levels and organised in 5 subgenera. Due to the high number of taxa, a lot taxonomists are trying to solve the problem of its classification and phylogeny but its natural classification still hasn’t been achieved. In this research, 60 individuals belonging to 4 taxa of the subgenus Dracunculus of Artemisia L. in Turkey were examined. For all the examined individuals from both the same and different populations belonging to the taxa of the subgenus Dracunculus, the sequences of the regions both psbA-trnH of chloroplast DNA and ITS of nuclear DNA were determined. Also, the gene regions obtained were recorded in the NCBI GenBank database and an accession number was taken. It was found that there was no gene flow and hybridization between the four studied taxa of the subgenus Dracunculus, and these 4 taxa also completed their speciation. According to the results of this molecular study, A. campestris var. campestris, A. campestris var. marschalliana and A. campestris var. araratica were proposed to be raised from the variety level to the species level. This research is important as it is the first molecular based study relating with the subgenus Dracunculus growing in Turkey. © 2022, Instituto Internacional de Ecologia. All rights reserved.
Uma investigação sobre o cloroplasto e os genomas nucleares de táxons pertencentes ao subgênero dracunculus (Bess.) rydb. de artemisia l. (asteraceae) na turquia
Keywords: Artemisia; CpDNA psbA-trnH; Phylogeny; R-DNA ITS; Turkey